2019
DOI: 10.1088/2515-7620/ab3d79
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous spring phenology shifts affected by climate: supportive evidence from two remotely sensed vegetation indices

Abstract: The Northern Hemisphere spring greenup (SG) has advanced between 0-12 days per decade since early 1980s as inferred from multiple satellite time series. The wide range of SG shifts is mainly due to the fact that these studies cover different periods and regions, and using different satellite records. Assessing the spatial heterogeneity of SG trends associated with different satellites is essential for robustly interpreting phenological dynamics and their responses to climate. We investigated the heterogeneity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…The shift in the seasonal LAI and SAI cycles was applied to boreal and temperate‐tree plant functional types (PFTs), where the annual maximum LAI was observed during June–September. The 5‐day perturbation of the seasonal cycle for the 15‐year simulation was reasonable considering the observed SOS and EOS trends (2–8 and 1–6 days decade −1 , respectively) derived from previous phenology studies focusing on the northern temperate and boreal regions (Piao et al., 2020; Xu et al., 2019). Two additional EOS sensitivity runs were performed with the same shift in LAI and SAI phenologies considering ±5 days during the senescence phase for 2000–2014.…”
Section: Methodssupporting
confidence: 86%
“…The shift in the seasonal LAI and SAI cycles was applied to boreal and temperate‐tree plant functional types (PFTs), where the annual maximum LAI was observed during June–September. The 5‐day perturbation of the seasonal cycle for the 15‐year simulation was reasonable considering the observed SOS and EOS trends (2–8 and 1–6 days decade −1 , respectively) derived from previous phenology studies focusing on the northern temperate and boreal regions (Piao et al., 2020; Xu et al., 2019). Two additional EOS sensitivity runs were performed with the same shift in LAI and SAI phenologies considering ±5 days during the senescence phase for 2000–2014.…”
Section: Methodssupporting
confidence: 86%
“…T he Arctic ecosystems are critical elements of the global carbon cycle and are greatly sensitive to ongoing warming (0.75 °C per decade during 1998-2012) 1 , which is more than twice faster than that for the rest of the globe. This warming has resulted in unprecedented changes across the region 2 , including spring greenup and snowmelt timings that are earlier by 4.3 and 5.5 days per decade, respectively 3,4 (with large variation, up to 12-14 days per decade, depending on local environmental conditions and vegetation species). Most research has focused on analyzing the role of rising temperatures in earlier greenup timings; however, recent studies showed that persistent snow cover that lasts until temperatures are warm enough for greenup (hereafter refer as "delayed snowmelt") results in delaying greenup, which exerts as strong a control as warming temperatures do, but in the opposite direction 5,6 .…”
mentioning
confidence: 99%
“…These greater slopes for the shrubs that were provided supplemental water suggested a more rapid canopy development (Park et al, 2015). Xu (2019) reported that increased precipitation occurring during the spring period regulated the sensitivity of the spring green up to warming spring temperatures. Others have noted a similar carry over effect from the previous year (Sala et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Forest canopies are dynamic living surfaces. Spectral reflectance of such surfaces have been shown to detect the ebb and flow of plant available water and associated vegetation responses, reflecting an ecological response to environmental variation (Pettorelli et al, 2005;Devitt et al, 2018) In addition, spectral reflectance can detect spring green up and leaf development and senescence associated with deciduous species (Kaye & Wagner, 2014;Park et al, 2015;Xu et al, 2019). Climate change has the potential to significantly alter these oscillations occurring at the plant and stand level, especially in the American southwest where growth and productivity of plants is strongly coupled to water availability (Bunting et al, 2017).…”
Section: Discussionmentioning
confidence: 99%